Portuguese websites obesity information - Martins, Diana (2012)
The internet is widely used by everyone as a source of health information, namely in obesity and weight lost. However, the easy production and edition of documents on the Internet enables any user to be an author and write the information according to their will, not ensuring the veracity of it. In this context the internet may be seen as a threat to one’s health. Thus, the aim of the study was to characterize and evaluate Portuguese websites obesity information and verify if the technical and scientific background of the author was related to the obesity information score of the websites. Portuguese 127 websites were evaluated with regard to obesity information, according to the Scottish Intercollegiate Guidelines Network Management of Obesity a national clinical guideline. The average score for information on obesity was 6.38 in 26 possible on websites aimed at children / young people and 3.51 in the 24 possible directed at adults. Of the websites examined 67% did not mention the technical training of the author and only 11% were authored by a Dietitian. This study shows that the score of obesity information was significantly higher in the sub-sample of the Dietitian or multidisciplinary team author. These results demonstrate the need to regulate the Internet as a source of health information, requiring the presence of a professional with technical training in healthcare.